(untitled) (Gestão & Regionalidade, 2024)
Corporate growth has been the object of attention since expanding business seems to evidence the success of organizational practices. However, this phenomenon needs to be examined considering that, from a critical perspective, the process implies politicization in order to avoid naturalizations and to consider the various agents and influences associated with it. In this article, our goal is to analyze the social representations of corporate growth from the perspective of workers, which was done through a qualitative research based on the professional trajectories of industrial workers in the metropolitan region of Belo Horizonte, treated through discourse analysis. Main results suggest that the workers perceive changes in the context and their consequences for the companies, resulting in the decision for corporate growth. However, the discourses are ambiguous, ranging from adherence to the idea that there is no way besides adapting, to combating the social effects of growth.